A next-generation system for smoke inhalation integrated with a breathing lung-on-chip to model human lung responses to cigarette exposure - Arunima Sengupta; Saskia Schmid; Noémie Grangier; Aurélien Dorn; Marco Hebestreit; Andreas Hugi; Kristína Žajdlíková; Anja Herbst; Paula Losada-Oliva; Heidi Ortolf-Wahl; Philippe Krebs; Janick D. Stucki; et al. (Scientific Reports)
Abstract Continuous exposure to cigarette smoke (CS) significantly contributes to the development and progression of chronic obstructive pulmonary disease (COPD) and lung cancer. Animal models that inhale smoke nasally and have different lung physiology from humans may not accurately replicate cigarette smoke-induced health effects. Furthermore, traditional in vitro models fail to replicate the lung’s dynamic mechanical forces and realistic inhalation exposure patterns, limiting their relevance in preclinical research. Here, we introduce an advanced smoke inhalation-based lung-on-chip system, the Continuous Flow AX12 (CFAX12), to investigate CS-induced cellular responses in a physiologically relevant manner. Unlike previous technologies, the CFAX12 integrates cyclic mechanical stretch with controlled whole-smoke exposure, allowing for a more accurate recreation of CS-induced alveolar microenvironment dynamics and barrier integrity responses. Using human alveolar epithelial cells, lung microvascular endothelial cells, and macrophages in mono- and co-culture models under air–liquid interface (ALI) conditions with breathing-like stretch (Str), we simulated key lung microenvironment features. Our results show that CS exposure using the CFAX12 induced a ~ 60% reduction in trans-barrier electrical resistance (TER), increased ROS generation depending on cellular model complexity, and a ~ 4.5-fold increase in IL-8 gene expression, all key hallmarks of early COPD pathogenesis. These findings underscore smoke-induced epithelial damage, inflammation, and oxidative stress, all of which contribute to alveolar barrier dysfunction and disease progression. Also, CFAX12 provides a more physiologically relevant alternative to submerged cigarette smoke extract (CSE) treatments, offering controlled whole-smoke exposure using the VC10 Smoking Robot, ensuring precisely regulated smoke delivery. Additionally, inclusion of pulmonary surfactant reduced IL8 gene levels by ~ 5 folds. Hence, by integrating mechanical and biological complexity, CFAX12 offers a robust platform for assessing inhaled smoke effects and identifying therapeutic targets. It’s application in COPD drug screening can facilitate the discovery of compounds that preserve alveolar integrity, reduce inflammation, and mitigate oxidative damage, ultimately bridging the gap between regulatory and preclinical research applications.